Attractive targeted sugar bait: the pyrrole insecticide chlorfenapyr and the anti-malarial pharmaceutical artemether–lumefantrine arrest Plasmodium falciparum development inside wild pyrethroid-resistant Anopheles gambiae s.s. mosquitoes - Raphael N’Guessan; Soromane Camara; Mark Rowland; Ludovic P. Ahoua Alou; Rosine Z. Wolie; Marius G. Zoh; Brou N’Guessan; Innocent Z. Tia; Welbeck A. Oumbouke; Matthew B. Thomas; Alphonsine A. Koffi (Malaria Journal, 2023)
Abstract Background Attractive targeted sugar bait (ATSB) is a novel approach to vector control, offering an alternative mode of insecticide delivery via the insect alimentary canal, with potential to deliver a variety of compounds new to medical entomology and malaria control. Its potential to control mosquitoes was recently demonstrated in major field trials in Africa. The pyrrole chlorfenapyr is an insecticide new to malaria vector control, and through its unique mode of action—disruption of ATP mediated energy transfer in mitochondria—it may have direct action on energy transfer in the flight muscle cells of mosquitoes. It may also have potential to disrupt mitochondrial function in malarial parasites co-existing within the infected mosquito. However, little is known about the impact of such compounds on vector competence in mosquitoes responsible for malaria transmission. Methods In this study, ATSBs containing chlorfenapyr insecticide and, as a positive control, the anti-malarial drugs artemether/lumefantrine (A/L) were compared for their effect on Plasmodium falciparum development in wild pyrethroid-resistant Anopheles gambiae sensu stricto (s.s.) and for their capacity to reduce vector competence. Female mosquitoes were exposed to ATSB containing either sublethal dose of chlorfenapyr (CFP: 0.025%) or concentrations of A/L ranging from 0.4/2.4 mg/ml to 2.4/14.4 mg/ml, either shortly before or after taking infective blood meals. The impact of their component compounds on the prevalence and intensity of P. falciparum infection were compared between treatments. Results Both the prevalence and intensity of infection were significantly reduced in mosquitoes exposed to either A/L or chlorfenapyr, compared to unexposed negative control mosquitoes. The A/L dose (2.4/14.4 mg/ml) totally erased P. falciparum parasites: 0% prevalence of infection in female mosquitoes exposed compared to 62% of infection in negative controls (df = 1, χ2 = 31.23 p < 0.001). The dose of chlorfenapyr (0.025%) that killed < 20% ...